Child psychology development in a changing society - Harwood, Robin L.; Miller, Scott A. 1944-; Vasta, Ross (John Wiley & Sons, 2008)
From the Publisher: In this comprehensive overview, readers will gain a better understanding of the various theories, perspectives, and research that characterize contemporary themes in child development. The book uses a contextual approach to examine the biological, cognitive, social, and emotional foundations of child development. Special attention is paid throughout to the contexts in which development occurs, including families and the larger culture, and how these intersect with our changing society.